The Association Between the Academic Level of Biology Education Students at A Private University and Their Level of Trust in Conspiracy Theories Related to COVID-19 - Fauzi, Ahmad (Muslim Education Review, 2022)
A low level of scientific literacy and application leads students to believe in conspiracy theories (CTs). The purpose of this study was to analyze the accuracy of biology education students’ responses to CTs about COVID-19 and its association with their academic level. The population of this survey research was 134 students at the Department of Biology Education, from a private university located in East Java, Indonesia. The research sample included twenty students with the highest GPA (high academic group) and twenty students with the lowest GPA (low academic group). A CT questionnaire about COVID-19 was used as a data collection instrument. Less than half of the students correctly answered five of the eight CT questions asked. Only four CT items had a response accuracy above 50 percent. Spearman’s rho test revealed that there was no significant correlation between GPA and students’ distrust of CTs. Based on the results of the Kruskal-Wallis H test analysis, the GPA of high and low academic students was significantly different. However, Chi-Square analysis showed that students’ distrust of all CTs asked was not significantly associated with students’ academic level. Concerning the findings of this study, it is necessary for suggesting to reformulate the curriculum for science and biology education to improve the scientific literacy and information literacy of prospective teachers.